Nghiên cứu ảnh hưởng của tỷ lệ tiền chất/ammoniac đến cấu trúc vật liệu chứa nanosilica - Ngọ, Đinh Thị; Phương, Hoàng Thị; Tiến, Hoàng Xuân; Thành, Nguyễn Trung (Vietnam Journal of Chemistry, 2016)
This study aimed to determine effect and relation between tetraethyl orthosilicate precursor (TEOS) and NH3 catalyst for nanostructured silica preparation through condensation method, based on their molar ratio. The nanostructured silica was prepared in mixed solution of NH3, ethanol, water with previous given calculations. The preparation was established at room temperature for 12 hours followed by filtering the as-synthesized precipitate. The precipitate was then dried and calcinated at 120 oC for 12 hours and at 600 oC for 3 hours, respectively for the final nanosilica containing products. A series of nanosilica containing samples were studied based on the molar ratios of TEOS/NH3, and the sample with the finest morphology was chosen for further characterizations. As the obtained results, the chosen sample with TEOS/NH3 of 1.5/1 existed in amorphous phase with particle size ranging from 12 nm to 25 nm. Some techniques were used such as SEM, TEM, EDX, FT-IR and UV-Vis for characterizing the morphology, element percentage, functional groups and silica absorption band respectively of the as-synthesized material.